2017
DOI: 10.1007/s00134-017-4807-z
|View full text |Cite
|
Sign up to set email alerts
|

Potentially modifiable factors contributing to sepsis-associated encephalopathy

Abstract: Acute renal failure and common metabolic disturbances represent potentially modifiable factors contributing to sepsis-associated encephalopathy. However, a true causal relationship has yet to be demonstrated. Our study confirms the prognostic significance of mild alteration of mental status in patients with sepsis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
232
8
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(258 citation statements)
references
References 38 publications
16
232
8
2
Order By: Relevance
“…This larger data observational study has mainly investigated the epidemiological and clinical characteristics of patients with SAE in a general ICU, although several studies have been reported on the epidemiological and prognostic features for SAE in ICU [1,12,13]. Our current study shown that the prevalence of SAE was similar to the epidemiological trend of sepsis, i.e., a peak of the prevalence of SAE was in the onset first day and following few weeks decreased over time.…”
Section: Discussionsupporting
confidence: 62%
“…This larger data observational study has mainly investigated the epidemiological and clinical characteristics of patients with SAE in a general ICU, although several studies have been reported on the epidemiological and prognostic features for SAE in ICU [1,12,13]. Our current study shown that the prevalence of SAE was similar to the epidemiological trend of sepsis, i.e., a peak of the prevalence of SAE was in the onset first day and following few weeks decreased over time.…”
Section: Discussionsupporting
confidence: 62%
“…In this study, we found that the prevalence rate of SAE within initial 48 hours accounted for 93.4 % of sepsis, and the main feature of SAE patients were presented with MODS (96.8%) driven by severe in ammatory storm. Previous studies shown that the prevalence of SAE was 53.0% to 87.0% of sepsis [9,10], and with 63% to 70% of hospital mortality [6,11]. However, our this study is clear: high prevalent SAE is almost near the epidemic rate of sepsis, which indicated the SAE was a leading life-threatening acute organ dysfunction and with 32.0% of fatality at initial 48 hours and 69.1% of fatality at initial 14 days.…”
Section: Discussioncontrasting
confidence: 55%
“…The third, a life-threatening brain failure is almost involved to MODS, and MODS (especially the brain) is the most vulnerable to hypoxia/ ischemia and oxidative stress caused by severe in ammatory storm [19,21]. The previous studies indicated that sepsis with MODS was more likely to exhibit a SAE [9,21,23,24].…”
Section: Discussionmentioning
confidence: 99%
“…However, in consistent with their conclusion, Na + did not indicate a meaningful predictive ability for death in patients with sepsis combined with AKI. The metabolic disturbances, including hypernatremia, hypercapnia and elevated lactates, caused by AKI in sepsis was associated with encephalopathy as well [29].…”
Section: Discussionmentioning
confidence: 99%